Lyme disease [ an evidence based approach - Halperin, John J. (Advances in molecular and cellular microbiology, 2011)
This book provides information on the advances in the application of molecular and cellular microbiology to Borrelia burgdorferi and Lyme disease. This book has 17 chapters and is divided into two parts. Part I covered the following topics: biology of tcks, vectors of Lyme disease, and of Borrelia; laboratory diagnosis of B. burgdorferi infection, antibiotic treatment and epidemiology. Part II focuses on the clinical aspects of Lyme disease.